2014
DOI: 10.1007/s00213-014-3767-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute tryptophan depletion reduces kynurenine levels: implications for treatment of impaired visuospatial memory performance in irritable bowel syndrome

Abstract: Manipulating peripheral tryptophan and kynurenine levels using ATD modulates hippocampal-mediated cognitive performance in irritable bowel syndrome but not healthy controls. These data may have important implications for reducing cognitive impairment in irritable bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 80 publications
0
16
0
2
Order By: Relevance
“…It was suggested that alternative pathways may also lead to memory impairments (e.g., LTP/NMDA related mechanisms). For example, ATD leads to lower kynurenic acid levels and has been associated with cognitive performance (Kennedy et al 2015). However, there is no clear evidence that the changes in kynurenic acid levels affect the cholinergic neurotransmission (e.g., Stone and Darlington 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that alternative pathways may also lead to memory impairments (e.g., LTP/NMDA related mechanisms). For example, ATD leads to lower kynurenic acid levels and has been associated with cognitive performance (Kennedy et al 2015). However, there is no clear evidence that the changes in kynurenic acid levels affect the cholinergic neurotransmission (e.g., Stone and Darlington 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the discussion above, it should also be noted that BIP has a selective affinity for the M1 and M4 receptors (Perez et al 2006), whereas ATD has a global effect on serotonin and kynurenine (Badawy and Dougherty 2016; Kennedy et al 2015). Even though in this study a selective and a global challenge were combined, both methods are assumed to act on different neurotransmitter systems in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated motor responses to food and, especially to lipids, have also been demonstrated in the small intestine in IBS 167 . Furthermore, tryptophan, the 5-HT precursor, and related compounds present in some foods could modulate psychological comorbidities and gastrointestinal symptoms in IBS 168 . Food-related symptoms could also be mediated through interactions between our diet, the products of digestion and the gut microbiota.…”
Section: Managementmentioning
confidence: 99%
“…Kynurenic acid inhibits inflammation in the 2,4,6‐trinitrobenzenesulfonic acid (TNBS) model of colitis in rats by blocking enteric NMDA receptors . Gut derived kynurenic acid may also have effects on the central nervous system by affecting mood and cognition …”
Section: Host Genetics Obesity Microbiome and Gut Healthmentioning
confidence: 99%